Development of Sustainability Instruments for Waste Alms Program (Sedekah Sampah) for Community Based Solid Waste Management in Sleman Regency, Yogyakarta - Ali, Abdulloh Rohman; Putra, Hijrah Purnama (Open Global Scientific Journal, 2025)
Background: Community-Based Waste Management Programs have been carried out in various regions in Indonesia, including Waste Alms (sedekah sampah). However, some waste management in Indonesia is no longer active without knowing the cause. Therefore, it is necessary to conduct a sustainability assessment to identify areas for improvement. To carry out the assessment, a sustainability instrument is needed as an assessment tool.Aims & Methods: This research aims to compile sustainability instruments and conduct trials of these instruments. Sustainability instruments are based on five aspects of community-based waste management and consist of 18 assessment indicators and assessment parameters. The instrument is compiled based on several references obtained. The locations used for the trial of this sustainability instrument are six waste alms locations in Sleman Regency. The calculation method used to determine the sustainability class and calculate the total value is the weighting method.Results: The results of the sustainability instrument trial were obtained. The Sido Rukun Waste Alms scored 74%, the Taruna Bakti Waste Alms scored 75%, and the Sedyo Luhur Waste Alms scored 71%. The three waste alms are included in the sustainable class. Meanwhile, the Rukun Makmur Waste Alms, the Rukun Lestari Waste Alms, and the Permata Waste Alms all receive scores of 83%. These three waste alms are included in the very sustainable class. The results of the sustainability instrument trial indicate that the sustainability instrument prepared can be used for the assessment of waste alarms in the future.